Evaluation des perturbations thyroïdiennes chez la femme diabétique dans la localité de Mostaganem - Bensaid, Soror (My University, 2019)
The association of diabetes and thyroid disorders is a common pathology in endocrinology. Thyroid disorders can have a major impact on glycemic control and untreated thyroid disorders affect the management of diabetes in patients. During the study period from 2018 to 31 March 2019, which took place in the two medical analysis laboratories Kharroubi; El chifa located in Mostaganem.657 consultations were recorded, among which 42 women were admitted for the association of 2 pathologies (diabetes-thyroid pathology). Based on the hormonal assay of TSH, FT4 and FT3 that was performed by an enzyme immunoassay Elisa, the results show a prevalence of 6.40% of thyroid disorders in the study population with a clear predominance of T2D in association with hypothyroidism, especially in menopause. Finally, a systematic approach to thyroid testing in diabetic patients is recommended.
Keywords: Thyroid disorders; Diabetes Type 2; TSH; T4; T3.